Novel Solid‐State Microbial Sensors Based on ZnO Nanorod Arrays. (12th March 2018) - Landry, Cody J.; Burns, Fraser P.; Baerlocher, Felix; Ghandi, Khashayar
Abstract: Gravity and magnetism are implemented to change the morphology of zinc oxide nanorod sensors during synthesis. The effects of gravity and magnetism can translate into future application of these nanorods through cost‐effective, environmentally friendly, and easy‐to‐use biosensor technology with the quickest available sensing. The sensors can pave the way toward detection of both bacteria and fungi present on the surface with high sensitivity. This ability to sense microorganisms in a "non‐solution‐based" environment represents a key step forward in the fields of health and food safety, as well as solid‐state nanomaterial biotechnology applications. Hundreds of thousands of people are affected each year by accidental contamination and current protocols are far from preventative. The results of the magnetic field studies when compared with previous results show that the following factors affect the outcome of applying magnetic field during the growth of nanorods on their morphology: the direction of growth with respect to gravity, the method of seeding, and the substrate. Abstract : The control over the morphology of ZnO nanoarrays is studied using a combination of the forces of gravity and magnetism. The size, shape, and order of ZnO nanorods can be tuned by changing the influence of these forces. This tuning of the nanoarray translates into optimization of their microorganism sensing properties as solid‐state, functionalization‐free biosensors to prevent contaminations.